Peningkatan Hasil Belajar Siswa pada Tema I Sub Tema III Materi Daur Hidup Hewan dengan Menggunakan Model Pembelajaran Kooperatif Tipe Stad Siswa Kelas III SDN 104211 Marindal - Rizky Arjuana Ritonga; Ulian Barus (Journal Innovation In Education, 2024)
This study aims to improve student learning outcomes in animal life cycle material using the STAD type cooperative learning model for grade III students at SDN 104211 Marindal, this type of research is Classroom Action Research which is carried out in 2 cycles, where each cycle consists of two meeting hours, namely 2 x 35 minutes. Data collection instruments are questionnaires and tests. The data obtained were analyzed using quantitative analysis leading to the calculation of the percentage of completion. Based on data analysis, the use of the STAD method in animal life cycle learning has increased. The results of the questionnaire from cycle I to cycle II increased by 12 (65.65%) with an average of 84.28 and increased in cycle 2 by 21 (93.35%) with an average of 89.33%. Thus, there was an increase of 9 students with a percentage of 27.72%. The conclusions of this study are: (1) The STAD type cooperative learning model can improve science learning outcomes in animal life cycle material. (2) To carry out learning with the STAD type cooperative learning model, teachers must be able to master the material and learning model so that students can be guided more actively.